DEA 모형을 통한 프로배구구단의 상대적 효율성 분석 - 박주호; Ju Ho Park; 원도연; Do Yeon Won; 정지명; Ji Myung Jung (Ch'eyuk kwahak yŏn'gu, 2014)
2005년 프로배구가 출범한 이후 그 인기와 관중추이는 꾸준히 증가해오다 2013년을 기점으로 하여 주춤하고 있는 상태이며, 적자에 허덕이는 구단은 효율적인 운영을 위한 노력보다는 단지 모기업광고를 위한 수단으로 구단을 운영하고 있다. 이러한 경영문제를 해결하기 위해 본 연구에서는 기존에 효율성 평가를 위해 사용하였던 자료포락분석(Data Envelopment Analysis)을 이용하여 국내 프로 배구구단들의 경영효율성을 평가하였다. 대상은 남자, 여자 프로배구 구단을 중심으로 진행되었으며, 분석을 위해 투입요소로는 선수운영비, 산출요소는 시즌 승점과 시즌 총관중수로 하였으며, 자료처리는 Frontier Analyst 4.0을 이용하였다. 결과는 첫째, 남자부의 경우 현대캐피탈, 러시앤캐시가 가장 효율적인 팀으로 평가되었으며, 비효율적인 팀은 삼성화재, LIG손해보험, 한국전력, 우리카드, 대한항공 순으로 나타났다. 둘째, 여자부에서는 GS칼텍스와 IBK기업은행이 효율적인 구단으로 나타났으며, 비효율적인 팀은 KGC인삼공사, 한국도로공사, 현대건설, 흥국생명순으로 나타났다. Professional volleyball league, which was launched and its popularity was steadily increased since 2005, has suffered from difficulties in its operation due to deficits after 2013. In addition, each professional volleyball team has worked out for parent company so far as a means of advertisement but does not look like effective management. Therefore, the purpose of this study was to evaluate each professional female and male volleyball team management efficiency through Data Envelopment Analysis. Player salary for the input variable and points and the number of spectators for output variable were used respectively then data were analyzed using Frontier Analyst 4.0. The results were as follows. First, Hyndai capital and Rush & Cash recorded the most efficient management among all professional male volleyball team. On the other hand, Samsung showed inefficient management, followed by LIG, KEPCO, Woori Card, and Korean Air. Second, GS Caltex and IBK were discovered as the highest management efficiency among all professional female volleyball team. On the contrary, KGC recorded inefficient management, followed by Korea Expressway Corporation, Hyundai Construction and Heungkuk life.